MARKETING OF POLITICAL SERVICES - Valdas Pruskus (Problemos)
Recently many references on marketing and application of its methods were published. However its application most frequently is related to economic field of the life (business), commonly with consumer goods market. Application of marketing in other fields of activities is not discussed although its methods are general and universal. So, the following questions arise. Are the statements of marketing such generalized and universal that they may be applied almost in all fields of the life or must they be modified taking into consideration the specific features of the field of activities. And if the second variant is true, what principles of marketing may be adopted and how must they be applied? And at first of all in the field which is the most important to us - the political activities, in the field of political services to the society. In the article it is tried to consider political services as a subject of marketing emphasizing the specific features and expression of the existence of political services.